2018
DOI: 10.1111/faf.12338
|View full text |Cite
|
Sign up to set email alerts
|

Estimating effective population size of large marine populations, is it feasible?

Abstract: Sustainable exploitation of marine populations is a challenging task relying on information about their current and past abundance. Fisheries‐related data can be scarce and unreliable making them unsuitable for quantitative modelling. One fishery independent method that has attracted attention in this context consists in estimating the effective population size (Ne), a concept founded in population genetics. We reviewed recent empirical studies on Ne and carried out a simulation study to evaluate the feasibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
97
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 51 publications
6
97
0
Order By: Relevance
“…Depending on the combination of threshold values, N e estimates varied by up to a factor of 7.5. In comparison, the well‐known effect of underestimation of N e due to ignoring overlapping generations is only around 30% in the thornback ray, independent of the census population size (Marandel et al, ). Further, the MAF threshold value (tested range 0.01 to 0.1) had a larger effect compared with the NA (tested range 25 to 50%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Depending on the combination of threshold values, N e estimates varied by up to a factor of 7.5. In comparison, the well‐known effect of underestimation of N e due to ignoring overlapping generations is only around 30% in the thornback ray, independent of the census population size (Marandel et al, ). Further, the MAF threshold value (tested range 0.01 to 0.1) had a larger effect compared with the NA (tested range 25 to 50%).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to SNP selection criteria, the sample size was found to impact estimates only slightly, given at least 50 individuals were used. Negative estimates are expected when sample size is insufficient (Marandel et al, ). Further, the 159 individuals were probably not enough to obtain stabilized estimates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike other marine species, such as Fenneropenaeus chinensis and Portunus trituberculatus, which have suffered too much human interference (for example, intensive catching and stock enhancement) in the northwestern Pacific (Liu et al, ; Song, Li, Zhang, & Gao, ), the S. marmoratus population has a large Ne (67.0 ‐∞), low genetic relatedness (<0.01) and a low level of inbreeding (<0.12). Moreover, Marandel et al () reported that negative Ne estimates are commonly occurred due to large population sizes in the marine environment when limited sample sizes were analyzed. Hence, the real Ne of S. marmoratus population seems to be greatly larger than we measured.…”
Section: Discussionmentioning
confidence: 99%